Visualization of COVID-19 Data in Yogyakarta City Using Data Studio - Cendana, Willy Pratama; Silmina, Esi Putri (SENATIK STT Adisutjipto, 2022)
The Corona virus, which has a very fast spread rate, has spread to all provinces in Indonesia, including in the Special Region of Yogyakarta. Information related to the development of COVID-19 data is needed by the government to handle COVID-19 cases. The purpose of this study is to visualize COVID-19 data in the form of Confirmed, Died, and Recovered data in the City of Yogyakarta, which later the results of the visualization can assist the government in making policies related to handling COVID-19 cases in the City of Yogyakarta. The research method used is visualization data processing using Data Studio, the data used is from October 2021 to January 2022. The result of the research is visualization of data in the form of a COVID-19 dashboard in the City of Yogyakarta which displays Confirmed, Died, and Recovered Cases. The visualization results show that in October and November, the graph results are quite high, while the graph in December, the Confirmed and Died graph is almost non-existent or zero, while the Healing graph is quite increasing.